How Madrasahs Build Students’ Character in Indonesia's Society 5.0 Era: Emerging Challenges - Achmad Zuhri; M Sofyan Alnashr; Hamidatun Nihayah; Ihsan Ihsan; Imam Khoirul Ulumuddin; Darnoto Darnoto; Siti Maryam Munjiat (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This study aims to analyze how madrasas develop students' character in the Society 5.0 era and to identify the various challenges and strategies implemented to strengthen moral values amid technological disruption. Using a qualitative case study approach, the research was conducted across three levels of madrasah education: Ibtidaiyyah, Tsanawiyah, and Aliyah. Data were collected through in-depth interviews with three madrasah principals, three deputy heads of curriculum who also serve as teachers, students, and parents, complemented by participant observation and document analysis. Data analysis followed the stages of data reduction, data display, and verification. The findings reveal that character education challenges in madrasahs are multidimensional, encompassing technological, social, cultural, and institutional factors. In response, madrasahs implement holistic and integrative strategies, including strengthening religious foundations, transforming Islamic values into social ethics, integrating local wisdom, developing character-based digital literacy, and fostering synergy among teachers, families, and communities. These strategies demonstrate that madrasahs operationalize SDG 4.7 by promoting ethical digital citizenship, moral responsibility, and humanistic values within a technology-driven learning environment. This study contributes to theory by expanding the understanding of how Islamic educational institutions contextualize global frameworks such as Society 5.0 and SDG 4 within local religious and cultural settings. In practice, the findings provide policy-relevant insights for educators and policymakers in designing adaptive, values-based character education models that support sustainable, inclusive, and high-quality education in the digital age.